2021
DOI: 10.1155/2021/4093895
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pore Structure on Kerogen Geomechanics

Abstract: Production stimulation techniques such as the combination of hydraulic fracturing and lateral drilling have made exploiting unconventional formations economically feasible. Advancements in production aspects are not always in lockstep with our ability to predict and model the extent of a fracturing job. Shale is a clastic sedimentary rock composed of a complex mineralogy of clay, quartz, calcite, and fragments of an organic material known as kerogen. The latter, which consists of large chains of aromatic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Moreover, Young’s modulus and Poisson’s ratio of the same kerogen type were comparable to other MD studies. 38 , 48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Young’s modulus and Poisson’s ratio of the same kerogen type were comparable to other MD studies. 38 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…PCFF+ has shown an ability to reproduce properties of organic-based materials as reported by different scholars in recent studies. 32 38 Having the force field defined, the final step is to integrate Newton’s equations of motion to predict particle trajectories inside the box during simulation.…”
Section: Molecular Modeling and Methodologymentioning
confidence: 99%
“…The ability of solid kerogen to undergo shrinkage was detected by Budinova et al [66] and Saad Alafnan [67]. Budinova et al found that solid kerogen could flow during heating even at low temperatures.…”
Section: Kerogen Microstructural Transformationmentioning
confidence: 96%
“…The linear portion of the stress–strain relationship is exploited to deduce the elastic constants, and the nonlinear domain informs the nature of plastic deformation kerogen failure. This general workflow was successfully applied to kerogen, delineating the factors influencing the geomechanics, 21 studying the interface between clay and organic materials, and the role of the contained fluid on the mechanical behavior of kerogen matter.…”
Section: Atomistic Modeling Of Kerogen Geomechanicsmentioning
confidence: 99%